Reflection of Post-World War II History in the Novel An English Murder By Cyril Hare - Adinda Jasmine Fachrunnisa; Agus Salim Mansyur; Agry Pramita (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
World War II was a major event that occurred in the past that had many impacts on human life, both in terms of economy, social, and culture. In addition, World War II also had an impact on literary works. Many writers criticized and expressed their emotions through literary works. One of them is the novel An English Murder by Cyril Hare which is set in the post-World War II era. This study aims to analyze how the novel An English Murder reflects what happened in Britain at that time using a qualitative descriptive method. Using Lucien Goldmann's theory of human facts, which emphasizes that literary works relate to the social structures that shape them, this study concludes that the novel An English Murder clearly depicts the social conditions in England after World War II. In addition, the research also shows that although An English Murder is a work of detective fiction, it manages to portray a broad social and political reality, as well as provide an overview of the problems that occurred in post-World War II Britain.